An Attempt to Systematically Revisit the Process of Conceptualization and Political Maturation of the Three Seas Initiative (3SI) - Andrea AMZA-ANDRÁS (Analele Universităţii din Oradea. Relaţii Internaţionale şi Studii Europene)
The main purpose of the study is to provide an informed and contextually relevant view of the Three Seas Initiative (3SI), which adds to the geographical and thematic cooperation formats already in place in the European Union (EU). This work tests the Initiative´s relevance and examines how it can contribute to the consolidation of the Eastern flank of the European Union, thereby strengthening the resilience in this part of Europe, which has been seriously shaken by the impact and consequences of the Russian invasion of Ukraine since 2022. The paper reflects on the role of the 3SI in the aftermath of the war on Ukraine and draws preliminary conclusions about the growth potential of the Initiative in the near future, both in political and geopolitical (integration of the Republic of Moldova and Ukraine) and in economic terms. The 3SI should not miss the momentum once the reconstruction of Ukraine effectively begins, and it should contribute substantially to the process of political and economic integration of the Eastern neighbourhood.